KINERJA PEGAWAI: PERAN MOTIVASI DALAM PENGARUH KOMITMEN DAN LINGKUNGAN KERJA - Yudiningtyas, Lutfi Agustina; Winarko, Ruddy (Jurnal Inspirasi Ilmu Manajemen, 2024)
The purpose of this study was to describe and analyze the influence of organizational commitment and work environment on employee performance through work motivation. This study was conducted at the Investment and One-Stop Integrated Service Office of Bojonegoro Regency with a population of 52 people, then the sample used was all members of the population using total sampling. Data were collected with a questionnaire and analyzed by Partial Least Square (PLS). The results of the study showed that performance and work environment were in good condition, and work environment were in high condition, Organizational commitment and work environment affect work motivation. Work environment has a direct impact on employee performance, while organizational commitment does not. Work motivation has a significant impact on employee performance, and both affect employee performance indirectly through work motivation.